Quality management in an agricultural research company in the brazilian Amazon - Araújo, Jamile da Costa; Freitas, Marcella Nunes de (Seven Editora, 2024)
The quality assurance process offers direction on how the team will oversee and confirm the standard of the project during its implementation.  This case study aims to analyze the quality management of Research, Development, and Innovation projects at a public agricultural research company unit in the Amazon, located in the state of Amapá. It will also investigate how specific regional characteristics affect project execution while identifying areas for improvement. The study uses qualitative and quantitative methods, and its findings will provide valuable insights for project managers and stakeholders in the field. Data from the corporate project management system was analyzed to verify project execution and identify obstacles. The system data was gathered from the reference Unit, Amapá, and three other research Units of the same company located in the North, Midwest, and South. Biased and emotional language was avoided in favor of a clear, objective narrative. The Cause and Effect Diagram and the Pareto Chart were utilized to prioritize the problems to be analyzed. Technical abbreviations such as Cause and Effect Diagram and Pareto Chart were introduced and defined upon their first use. The document adhered to standard academic structure, formatting, and citation methods. Finally, the 5W2H technique was employed to develop the action plan. Project management is conducted in a standardized manner with monitoring taking place every four months. The primary cause of delays in project activities at the Reference Unit is a shortage of materials, supplies, and equipment during the scheduled period. This issue is mainly attributed to delays in the transfer of financial resources and the challenge of acquiring these items. The action plan recommends diversifying funding sources, modifying the physical-financial schedule, and providing training to teams in risk management and procurement management. DOI:https://doi.org/10.56238/sevened2024.014-017